Electronic properties and surface reactivity of SrO-terminated SrTiO3 and SrO-terminated iron-doped SrTiO3. Issue 1 (31st December 2018) - Staykov, Aleksandar; Tellez, Helena; Druce, John; Wu, Ji; Ishihara, Tatsumi; Kilner, John
Abstract: Surface reactivity and near-surface electronic properties of SrO-terminated SrTiO3 and iron doped SrTiO3 were studied with first principle methods. We have investigated the density of states (DOS) of bulk SrTiO3 and compared it to DOS of iron-doped SrTiO3 with different oxidation states of iron corresponding to varying oxygen vacancy content within the bulk material. The obtained bulk DOS was compared to near-surface DOS, i.e. surface states, for both SrO-terminated surface of SrTiO3 and iron-doped SrTiO3 . Electron density plots and electron density distribution through the entire slab models were investigated in order to understand the origin of surface electrons that can participate in oxygen reduction reaction. Furthermore, we have compared oxygen reduction reactions at elevated temperatures for SrO surfaces with and without oxygen vacancies. Our calculations demonstrate that the conduction band, which is formed mainly by the d-states of Ti, and Fe-induced states within the band gap of SrTiO3, are accessible only on TiO2 terminated SrTiO3 surface while the SrO-terminated surface introduces a tunneling barrier for the electrons populating the conductance band. First principle molecular dynamics demonstrated that at elevated temperatures the surface oxygen vacancies are essential for the oxygen reduction reaction. Abstract :